English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x-5=6
3x-2y=5

can some one describe and show me how

2006-11-05 15:29:53 · 12 answers · asked by ourdoorsangler 1 in Science & Mathematics Mathematics

12 answers

Notice the first equation only involves x.
x - 5 = 6
Add 5 to both sides
x = 11
Now replace x with 11 in the second equation
3(11) - 2y = 5
33 - 2y = 5
-2y = 5 - 33
-2y = -28
y = -28/-2
y = 14
Answer: (11,14)

2006-11-05 15:32:54 · answer #1 · answered by MsMath 7 · 4 2

x-5=6
3x-2y=5

you can say that
x-5=6

is the same as

x = 11 (add the five to the right of the = sign)

then you take the x value and plug into second equation

3x-2y=5
3 (11) - 2y = 5
33-2y=5
5-33 = -2y
-28 = -2y
y = 14

2006-11-05 23:36:18 · answer #2 · answered by aplpie 3 · 3 1

Let's start with this equation:
x-5=6

Add 5 to both sides:
x=11

Now, take x=11 and substitute it for 3x-2y=5:
3(11)-2y=5
33-2y=5

Subtract 33 on both sides:
-2y=-28
y=14

(11,14)

Check:
11-5=6
6=6

3(11)-2(14)=5
33-28=5
5=5

I hope this was helpful!

2006-11-05 23:41:06 · answer #3 · answered by Anonymous · 1 1

x - 5 = 6
x = 11
substitute into the second equation:
3(11) - 2y = 5
33 - 2y = 5
-2y = 5 - 33
-2y = -28
y = -28/-2
y = 14 !

2006-11-08 12:16:33 · answer #4 · answered by locuaz 7 · 2 1

Surely the first one is meant to be
x - 5y = 6 ??

[otherwise you would just say x = 11, sub in the second one and get
y = 14]

Look for a term whose coefficient is 1. In this case, it's x, so make x the subject of the first equation by adding 5y to both sides.

x = 6 + 5y.

"substitute" just means that in the other equation you replace x by
6 + 5y, i.e. it becomes

3(6 + 5y) - 2y = 5

I expect you know how to remove brackets from this, collect terms and solve for y.

Whatever value you get for y (?maybe 1?), sub this in
x = 6 + 5y
and you've solved it.

2006-11-05 23:37:34 · answer #5 · answered by Hy 7 · 2 1

x-5=6 ad 5 to each side
x=11

3x-2y=5 substitute x=11
3*11-2y=5
33-2y=5
33-5=2y
y=14
x=11

2006-11-06 00:16:57 · answer #6 · answered by yupchagee 7 · 3 1

since x-5=6

then x=6+5: x=11

we now have the value of x, so we plug it in the 2nd equation

3x-2y=5
3(11)-2y=5
33-2y=5
33-5-2y=0
28=2y
y=14

the pluging in procedure is called substitution
hope that helps =)

2006-11-05 23:38:10 · answer #7 · answered by Grand Phuba 5 · 3 1

Solve the top equation for x to get x=11; next, substitute x=11 into the bottom equation: 2*11-2y=5 to get 22-2y=5 to get -2y=-17 to get 2y=17....y=8.5.

2006-11-05 23:35:44 · answer #8 · answered by bruinfan 7 · 0 5

i think it's x-5y=6 => x = 5y + 6
3(5y + 6) - 2y = 5 => 15y + 18 -2y = 5
13y = -13
y = -1
x = 1

2006-11-05 23:46:12 · answer #9 · answered by Anonymous · 0 3

x=11
sub
33-2y=5
-2y=-28
y=14

2006-11-05 23:32:55 · answer #10 · answered by raj 7 · 3 2

fedest.com, questions and answers